Relationship between Pregnancy and Lactation Status and De Quervain's Syndrome - Naim, Karimatun; Wahyuni (Indonesian Journal of Medicine, 2024)
Background: De Quervain's Syndrome is a collection of symptoms accompanied by inflammation and pain in the tendon sheath that covers the extensor pollicis brevis and abductor pollicis longus muscles. These symptoms appear as a result of cumulative (repeated) microtrauma and overuse causing malfunction of the tendon sheath. Cause of De Quervain's Syndrome is still not known for certain. Due to hormonal factors, it is more common in pregnant women and most common in people aged 30 to 55 years. This study aimed to examine the relationship between pregnancy and lactation on the incidence of de Quervain' syndrome. Subjects and Method: This was an observational study conducted at the PDHI Islamic Hospital, Yogyakarta, from August to September 2023. Total sample of 70 third trimester of pregnant women or lactating mothers who had children aged 1 month to 1 year was selected purposively. The dependent variable was De Quervain's syndrome. The independen variable was pregnancy and lactation. The data were collected using a questionnaire and analyzed by Chi square test. Results: Pregnancy and lactation reduced the risk of de Quervain's syndrome (OR= 0.34; 95% CI= 0.125 to 0.907; p=0.029). Conclusion: Pregnancy and lactation reduced the risk of de Quervain's syndrome.